2013
DOI: 10.1017/s1068280500004962
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Influencing a Hospital's Decision to Adopt a Farm-to-Hospital Program

Abstract: Farm-to-hospital (FTH) programs can potentially improve the economy of local communities and preserve the environment. Research on adoption of farm-to-hospital (FTH) programs is extremely limited in the agricultural and applied economics literature. Using data from our 2012 regional FTH program survey of hospital food-service directors in the Northeastern United States and from the U.S. Department of Agriculture, this study estimates a logit model to determine factors that influence a hospital's decision to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…As noted previously, Smith, Kaiser, and Gómez (2013) found that research on the adoption of farm to hospital programs was "extremely limited" and "nearly nonexistent" (p. 38). Further, they noted that independent factors that might influence a hospital's decision to adopt local food programs have not been explored.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As noted previously, Smith, Kaiser, and Gómez (2013) found that research on the adoption of farm to hospital programs was "extremely limited" and "nearly nonexistent" (p. 38). Further, they noted that independent factors that might influence a hospital's decision to adopt local food programs have not been explored.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, Kaiser Permanente (2013), The Nation (Klein, 2012), and numerous other articles and news reports have covered the phenomenon. However, these popular media articles and informally published reports are backed up by very few articles from scientific peerreviewed journals (Clancy, 2013;Ritchie & Chen, 2011;Smith, Kaiser, & Gómez, 2013). Of those that were available, most were very small and geographically concentrated.…”
mentioning
confidence: 99%
“…Table 2 provides a summary of the study characteristics of the included studies, all of which were published between 2011 and 2018. Most studies (seven out of nine) were conducted in the United States 11,23–27,29 . Most studies (seven out of nine) involved a qualitative research design ( n = 7), 11,23,24,26–29 whereas two papers described case‐study evaluations 25,30 .…”
Section: Resultsmentioning
confidence: 99%
“…A variety of factors motivate institutions to purchase directly from SFV farms. For many institutions, buying direct from an SFV farm is thought to offer benefits, such as supporting the viability of the local agricultural sector, offering social connections and economic support for the community, and providing perceived environment and sustainability benefits (Martinez et al, 2010; Smith et al, 2013; HWH, 2017). In terms of health, two characteristics of nutrition available from produce support a model of local sourcing.…”
Section: Overview Of the Small-farm To Institution Marketing Channelmentioning
confidence: 99%